Hubungan Konsumsi Minuman Kemasan dengan Kejadian Overweight pada Siswa/i SMKN 1 Kota Jambi - Arupia Karolin , Mey Artha; Wulansari, Arnati; Fati Hatussaadah, Siti (Prosiding Seminar Kesehatan Nasional, 2024)
Overweight is a nutritional problem in adolescence. Overweight is the result of a person's interaction with their environment, which over time shapes inappropriate habits or behaviours. One of these is excessive consumption of packaged beverages. Beverages that are packaged are those that have simple sugars added during the manufacturing process, which increases the energy content but has a low content of other nutrients. The purpose of this study was to determine the relationship between the consumption of packaged beverages and the incidence of overweight among students of SMKN 1 Jambi City. This study is a quantitative study using cross-sectional method. This research was conducted from March to May 2024. The population in this study were 1224 students of SMKN 1 Jambi City with a sample size of 88 people. This research instrument used the SQ-FFQ questionnaire and anthropometric measurements of nutritional status with the IMT/U Z-score indicator. Sampling in this study was done using simple random sampling technique. Data analysis was univariate and bivariate using the Spearman rank correlation test. The results showed that 56.8% of the respondents were frequent consumers of packaged beverages and 37.5% of the respondents were overweight. The results of the Spearman rank correlation test between the consumption of packaged beverages and the incidence of overweight showed a P value of 0.001. There is an association between the consumption of packaged beverages and the incidence of overweight.